Persepsi Siswa dan Guru Terhadap Implementasi Program Sholat Dhuha Sebagai Upaya Pembentukan Karakter Religius di Sman 79 Jakarta - Riska Ramadhani; Ananda Husain Al Hafifi; Andre Prayoga Mardian; Farinsyah Malik; Khairil Ikhsan Siregar (Advances In Education Journal, 2025)
This study examines the implementation of the sholat dhuha program at SMAN 79 Jakarta and its contribution to students’ religious character. Using a qualitative approach, data were collected through interviews, observations, and documentation involving participating students and the Islamic Education teacher. The findings show that the program is conducted in a structured and scheduled manner with teacher supervision and adequate facilities, although challenges such as lack of concentration and inconsistent participation remain. Students perceive the program as beneficial in building discipline in worship, strengthening spirituality, and improving social interaction. Teachers view it as effective in fostering obedience, tolerance, and positive religious behavior. Overall, the sholat dhuha program plays an important role in developing students’ religious character, though further improvement is still needed.